A tri‐band spoof surface plasmon polaritons based antenna for endfire radiation. Issue 7 (30th March 2021) - Sarkar, Sayan; Gupta, Bhaskar
Abstract: This article proposes a planar antenna, which exhibits endfire radiation patterns at three distinct frequency bands. The main radiator consists of a coplanar waveguide fed comb‐shaped spoof surface plasmon polaritons based antenna placed on top of a microwave substrate. An L‐shaped stub like structure is added to the bottom of the substrate and is coupled electromagnetically to the main radiator. The resulting antenna operates in three frequency bands. It achieves endfire radiation between 7.6 and 7.75 GHz (first band), 8.4 to 8.68 GHz (second band) and 12.4 to 13 GHz (third band) with maximum measured gains of 7, 7.5, and 7.7 dBi respectively. The antenna has a maximum simulated efficiency of 86% at 7.7 GHz, 96% at 8.5 GHz, and 92% at 12.6 GHz. The structure also exhibits frequency dependent endfire beam scanning within the 12.4 to 13 GHz band in the xy plane (plane of the antenna), achieving a total scan range of 21 0 from phi = −19 0 to phi = 2 0 .